Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1111/j.2042-7158.1991.tb03479.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of Gastrointestinal Mucosal Damage by Salicyluric Acid Compared with Salicylic Acid in Rabbits

Abstract: The gastrointestinal mucosal damage following the oral administration of salicylic acid or salicyluric acid was examined in rabbits using a scanning electron microscope. Six and 24 h after treatment with salicylic acid, morphological changes of gastric mucosa were recognized. In rabbits treated with salicyluric acid, however, severe damage in the gastric mucosa was not found after 24 h compared with the treatment with salicylic acid. Following the treatment with salicylic acid, some mucosal damage in the duode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…The existence of salicyluric acid has been reported in milk (Booth et al 1962). It can be metabolised to salicylic acid by intestinal microorganisms (Nakamura et al 1991), which has been shown to have CRC preventive traits (Paterson and Lawrence 2001). In our study, more salicylate was excreted in the urine of rats on LPW diet compared with LPM.…”
Section: Q4supporting
confidence: 50%
“…The existence of salicyluric acid has been reported in milk (Booth et al 1962). It can be metabolised to salicylic acid by intestinal microorganisms (Nakamura et al 1991), which has been shown to have CRC preventive traits (Paterson and Lawrence 2001). In our study, more salicylate was excreted in the urine of rats on LPW diet compared with LPM.…”
Section: Q4supporting
confidence: 50%